Hukum Islam, HAM dan Maqashidu Asy-Syari’ah: Upaya Menyatukan Jasad dan Ruh - Nahe’i Nahe’i (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
One debate that will not be finished is a debate about the relationship between human rights and Islam. Even though the Cairo Declaration was established which declared human rights in Islam and also declared the efforts to transform human rights into the National Law. It does not end, especially among "conservative Muslims". There are several questions regarding that debate, they are, are human rights contradict to Islam because it is the product and agenda of the West? Or is it support to Islam? Or is it precisely the substance of Islam itself? These questions have arisen along with the strengthening of populism, identity politics, and politicization of religion (ad-din al-musayyas). This paper tries to look at human rights within the framework of maqhashidus syari'ah, because the compatibility of human rights and Islam can be seen only by this approach. Maqhashidus syari’ah here is a concept that developed over time in line with changes in human civilization. This paper assumes that there are some points where human rights and Islam can be connected, but there are also some points difficult to be connected.